The Role of Clinical Registries in Monitoring Drug Safety and Efficacy - Reid, Christopher (Elsevier Ltd, 2015)
© 2015 Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) and the Cardiac Society of Australia and New Zealand (CSANZ). The last 20 years has seen a rapid growth in the area of clinical registries to monitor the safety and quality of healthcare delivery across the globe. Clinical registries have predominantly focussed on tertiary care service delivery, often procedurally based and directed to identifying variation in patient outcomes. They are also often used to determine whether evidence-based therapeutic guidelines are being adopted and whether safety signals are being identified when novel therapies are first released into clinical practice. This paper will examine the role of clinical quality registries as a pharmacovigilance methodology for the 21st Century.